The Impact of Audio-Visual Media toward Learning Result in the Subject of Seizing Picture - Cahyono, Dwi Nur; Khumaedi, M; Hadromi, Hadromi (Journal of Vocational and Career Education, 2021)
The development of the learning model aimed to create learning conditions that facilitate students to be active and enjoy every learning process so that the students can optimize their achievement. One of the support tools to create an ideal learning atmosphere was learning media. The aimed of this study were to understand the impact of audio-visual media in seizing picture subject between two groups of students. This research applied Research and Development (RD) approach. The participants consist of 2 lecturers with media expertise, 2 teachers, and 34 students of the X grade students of Light Vehicle Engineering who were selected randomly. The finding showed that there was a significant difference in the learning result. The experiment group that used audio-visual media achieved 83,24% (very high categories), while the control group that used written material achieved 49,43% (adequate-category). Based on the result above, it can be concluded that audio-visual media can improve students' competency in seizing pictures subject.